The rights of passengers in a public bus: the relevance of imposition statutory liability for bus drivers / Mohd Zulhilmi Ibrahim and Muhammad Hidayat Wahab. - Ibrahim, Mohd Zulhilmi; Wahab, Muhammad Hidayat (2007)
The rights of passengers in a public bus had become a heatedly debated issue ever since the increasing number of case of accidents which usually cause death and injury to a large number of peoples (mass killing). In Malaysia, the only specific statute that governing the liability of bus driver is Road Transport (Amendment) Act 1999 which specifically enacted to accommodate the legal issues pertaining to road transport in general. This research is conducted to find out whether the statutory liability should be impose to the negligence' bus driver. Its also looks into the problems which have been encountered in providing legal protection to the individual for injury and death caused by negligence' bus driver. We also examine the weaknesses of the existing law such as the adequacy of punishment and the potential harm which may result from it. Our research is based on qualitative methodology where we conduct a library and internet research to gather the relevant information and to try to contradict it with the current statute and figure out for better alternative law. The research aim to answer three questions namely; should statutory liability be imposed to the negligence' bus drivers in situation where the passengers suffered fatal injury and died, is the provisions in section 41 and section 43 of Road Transport (Amendment) Act 1999 pertaining to punishment of road transport offence in general sufficient in remedy the victim and their deceased and should the current legal sanction of negligence' bus drivers be varied to uphold the justice and rights of bus passengers. This research also proposes imposition of strict liability to the bus driver and bus company towards the bus passenger where rule under Rylands v Fletcher which is limited to matter of nuisance should be extend to the scope in accident. Thus, we hope that this provision will protect and safeguard the rights of the bus passengers.